Clinical adjacent segment pathology after anterior cervical discectomy, with and without fusion, for cervical degenerative disc disease: A single center retrospective cohort study with long-term follow-up - Valérie N.E. Schuermans; Anouk Y.J.M. Smeets; Nienke P.M.H. Wijsen; Inez Curfs; Toon F.M. Boselie; Henk van Santbrink (Brain and Spine, 2022)
Introduction: Clinical adjacent segment pathology (CASP) continues to be a cause of concern after anterior surgical treatment for single- or multilevel cervical degenerative disc disease (CDDD). The current literature reports inconsistent incidence rates and contended risk factors in the development of CASP. Research question: The aim is to determine the incidence of additional CASP-related surgeries after anterior cervical discectomy with fusion (ACDF) or without fusion (ACD) for CDDD. Secondary outcomes include risk factors for the development of CASP and long-term clinical outcomes. Materials & methods: This is a single-center, retrospective cohort study with a long-term follow up. Patients undergoing ACD(F) for CDDD between January 2012 and December 2019 were included. Results: A total of 601 patients were included, with an average follow-up period of 5.0 years. Most patients underwent ACDF with stand-alone cages (87.7%). CASP developed in 58 (9.7%) patients, 41 (70.7%) of which required additional adjacent level surgery. ACD significantly accelerated the development of CASP. The C2–C7 Cobb angle appeared less lordotic upon early post-operative imaging in ACDF patients that later-on developed CASP. Baseline degeneration at the index level and adjacent levels was not significantly different between patients with and without CASP. Discussion & conclusion: In this retrospective cohort, we observe a relatively low rate of additional surgery for CASP in ACDF with stand-alone cages. We suggest that surgical technique, fusion, segmental kyphosis and natural degeneration play a multifactorial role in the development of CASP. Complication rates were low and clinical outcomes were similar for all techniques used.